Exploring transformative learning opportunities as part of the delivery of a video-based intervention - Collins, Luke C.; James, Deborah M. (Equinox, 2011)
A teacher of the deaf reported a change in perspective following her involvement as a participant in a therapeutic intervention known as video interaction guidance (VIG). We applied a model of transformative learning to validate this report and to explore how this process was initiated. We analysed the transcriptions of two video selections from a 35 minute therapy intervention session with the teacher of the deaf for indicators of stance. The teacher of the deaf’s change in stance is mapped in her discourse throughout the session to explore this learning process. The proposition is that particular discourse components can trigger a transformative learning process. Our analysis showed that the participant frequently used binary distinctions to structure their talk subsequent to the guide having introduced a dialectic exploration of a binary proposition. The object of the learning extends beyond the video component as the participant situates this learning in their wider communicative practices. We explore the ways in which the intervention facilitated this learning process and discuss the ways in which the potential for learning can be maximised.